MODERN APPROACHES TO ASSESSING CORRUPTION RISKS: ANALYSIS OF KEY INDICATORS - Dluhopolskyi, Oleksandr (Socio-economic relations in the digital society, 2024)
The work examines modern approaches to the assessment of corruption risks in three blocks: aggregated indices, expert assessments, and surveys of the opinion of the public and business representatives. The conducted analysis of each indicator in the context of its advantages and disadvantages and sources of collected information are displayed and systematized in tabular form. It is noted that it is not possible to make cross-country comparisons for all indicators due to the small sample of some of them, the indirect relationship of certain indicators to corruption risks, the subjectivity of surveys or the imperfect methodology of their construction, which is only gradually improving. The work uses methods of comparative analysis and visualization using VOSviewer, which made it possible to cluster the topic of corruption, to demonstrate in a visual form the key researchers of this phenomenon by surnames and countries of origin. Reasonable advantages of the flexibility that today’s wide palette of existing indicators provides to scientists to deepen and combine them in the direction of a specific study, as well as to develop their own indices and methods for assessing corruption risks on a global scale. The development of a universal indicator for the assessment of corruption risks is predicted for the future.